(NkLOD dEB@SSIs (NMONOGRAFIQs - (N`(B. (NkREMLEWs ((NmOSKWAs (NmUZYKAs, 1965)
(NiMQ kLODA dEB@SSI DLQ RUSSKIH DOROGO(B. (NsWQZI EGO TWOR^ESTWO S RUSSKOJ KULXTUROJ GLUBOKI I MNOGOSTORONNI(B.s
Keywords: (NMONOGRAFIQs